The Position of the United Tent Party in Iraq in the Relative blocs and International Alliances (1949-1954) (Journal of the College of Basic Education, 2022)
The phenomenon of regional blocs and Western alliances is an important part of European colonialism's orientations and policy tactics in the Arab region, which prevailed during World War II. Iraqi parties also considered that this phenomenon represents a new colonial policy as an alternative to colonial policy.